Chitosan derived N-doped carbon coated SnO2 nanocomposite anodes for Na-ion batteries - Aydin, Meral; Demir, Emrah; Unal, Burcu; Dursun, Burcu; Ahsen, Ali Sems; Demir-Cakan, Rezan (Elsevier, 2019)
Nitrogen doped hard carbons are synthesized from chitosan via hydrothermal carbonization (HTC) followed by further carbonization process at different temperatures (500, 750, 1000 degrees C). Those carbons are investigated as sodium ion battery anode materials. Latter, under HTC conditions, SnO2 nanoparticles are incorporated with carbon source to obtain SnO2/C composite. The influence of binders (carboxymethyl cellulose (CMC) and poly (vinylidene fluoride) (PVDF)) on the cyclic performance are investigated in which better cycling performances are achieved with PVDF. Indeed, electrochemical impedance spectroscopy test results reveal that the electrode prepared with PVDF has lower charge transfer resistance than that of CMC binder. Sodium ion diffusion coefficient values in the presence of CMC and PVDF are calculated from the Nyquist plot to be 4.35 x 10(-11) and 3.06 x 10(-10) cm(2)/s after 50 cycles, respectively.
Keywords: Hard carbon; Nitrogen doped carbon; Chitosan; Tin oxide; Hydrothermal carbonization; Sodium ion batteries